2003
DOI: 10.1089/089277903321196788
|View full text |Cite
|
Sign up to set email alerts
|

Objective and Subjective Changes in Patients with Peyronie's Disease after Management with Shockwave Therapy

Abstract: Our study demonstrates objective and subjective changes in patients with Peyronie's disease after shockwave therapy. Artificial erection served as a control to assess improvement of the deviation angle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 11 publications
2
27
0
Order By: Relevance
“…Extracorporeal shock-wave therapy (ESWT) has been adopted for the treatment of PD over the last decade [79,80] . Previous investigations reported improvement of nearly all symptoms associated with PD.…”
Section: Extracorporeal Shock-wave Therapymentioning
confidence: 99%
“…Extracorporeal shock-wave therapy (ESWT) has been adopted for the treatment of PD over the last decade [79,80] . Previous investigations reported improvement of nearly all symptoms associated with PD.…”
Section: Extracorporeal Shock-wave Therapymentioning
confidence: 99%
“…The few studies that have reported on the effects of ESWT on penile rigidity have failed to find a difference. 14,19,20 Given the availability and efficacy 21 of medical therapies for ED, it is our practice to offer these methods to men with combined PD and erectile dysfunction prior to considering ESWT. Those who show a good response and achieve near-normal penile rigidity are offered ESWT.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that pretreatment and post-treatment measurements of an artificial erection provide the best objective measure of changing curvature. 19 Although we acknowledge the value of objective assessments in a trial setting, we have taken a more pragmatic approach. For a treatment to be clinically useful, it is essential that the patient regard it as a success.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9][10][11] Many of the studies have been criticized for their lack of objectivity and relatively short follow-up periods (mean follow-up 1-9 months), and there is, therefore, a paucity of longterm data with regard to therapy effectiveness and safety. There also is a lack of information regarding the long-term durability of the response after initial success.…”
Section: Srirangam Et Al 882mentioning
confidence: 99%
“…The use of extracorporeal shockwave therapy (ESWT) for Peyronie's disease was introduced by Bellorofonte and associates 1 as a conservative option, and since then, numerous reports have addressed the efficacy of this treatment. [2][3][4][5][6][7][8][9][10][11] Reported results have been discordant, with some showing promising responses to ESWT with reductions in deformity, plaque size, and pain and concurrent improvement in sexual function, whereas others demonstrate no significant benefit. 8,10,11 In spite of reports of success and low complication rates, previous studies have been criticized for small patient numbers, absence of a control arm, use of subjective outcome measures, and lack of long-term follow-up.…”
Section: Introductionmentioning
confidence: 99%